Presence of trauma and suicide risk: Personal control as a moderator. Issue 8 (14th September 2018) - Chang, Edward C.; Lucas, Abigael G.; Chang, Olivia D.; Duan, Tianbi; Zhou, Zihao; Yang, Jeff Z.; Morris, Lily E.; Angoff, Harrison D.; Hirsch, Jameson K.
ABSTRACT: Given past findings that have linked trauma and lack of personal control to greater suicidal risk in adults, the present study examined how trauma presence and personal control are uniquely involved in predicting suicidal risk in a sample of 469 college students. Regression analyses indicated that both trauma presence and personal control were significant predictors of suicidal risk, as was their interaction. The present findings suggest a need to consider both trauma presence and low personal control in assessing for suicidal risk in college students.